2012
DOI: 10.1007/s00244-012-9852-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pesticide Contamination on Aquatic Microorganism Populations in the Littoral Zone

Abstract: The effect of pesticide contamination of the littoral zone on the population of bacteria and fungi was analyzed using the example of a eutrophic water reservoir exposed for >30 years to the influence of expired crop-protection chemicals, mainly DDT. For three consecutive years, quantity analyses of bacteria and fungi were conducted and the composition of the microorganism population analyzed against seasonal dynamics. Mold and yeast-like fungi were also isolated and identified. Within the Bacteria domain, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 67 publications
2
12
0
Order By: Relevance
“…A similar finding was reported by Lew et al (2013) that reported that the presence of pesticides can limit the occurrence of fungi and bacteria in the aquatic environment. In terms of the fungi identified, A. fumigatus is the only species in common between the two studies (this study and the study conducted by Lew et al (2013)). Besides being able to resist to a constant input of atrazine, diuron, isoproturon and chlorfenvinphos (in this study), A. fumigatus was also found to resist to the presence of DDT in the lakes sampled by Lew et al (2013).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…A similar finding was reported by Lew et al (2013) that reported that the presence of pesticides can limit the occurrence of fungi and bacteria in the aquatic environment. In terms of the fungi identified, A. fumigatus is the only species in common between the two studies (this study and the study conducted by Lew et al (2013)). Besides being able to resist to a constant input of atrazine, diuron, isoproturon and chlorfenvinphos (in this study), A. fumigatus was also found to resist to the presence of DDT in the lakes sampled by Lew et al (2013).…”
Section: Discussionsupporting
confidence: 84%
“…A possible reason for this observation is probably the toxicity exerted by the pesticides that may affect the survival of certain species (Lo 2010) or that the reactor population entered into a nutrient shortage enabling only the resistant species to survive (Tripathi et al 2013). A similar finding was reported by Lew et al (2013) that reported that the presence of pesticides can limit the occurrence of fungi and bacteria in the aquatic environment. In terms of the fungi identified, A. fumigatus is the only species in common between the two studies (this study and the study conducted by Lew et al (2013)).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, the metabolic mechanism of DDT degradation in microorganism is not clear. Under the influence of long-term exposure to DDT, microorganisms can adapt to the presence of this pesticide (Lew et al, 2013), allowing it to accumulate and be serially transferred to higher levels in the food chain (ATSDR, 2002). Therefore, the analysis of the metabolism of DDT in aquatic microorganism (e.g., protozoa, bacteria) is important.…”
Section: Introductionmentioning
confidence: 99%